N017 The impacts of an inflammatory bowel disease nurse specialist on quality of care and costs in Finland. (16th January 2018) - Toivonen, T; Jussila, A; Kolho, K -L; Molander, P
Abstract: Background: The increasing burden of inflammatory bowel disease (IBD) causes growing need for health care resources. Although specialised IBD nurse is considered a valuable and cost-effective member of a multidisciplinary team, only some clinics responsible for IBD care employ such nurses. We evaluated the impact of an IBD Nurse on the quality of care and cost effects of IBD patients in Finland. Methods: The impact of an established IBD Nurse to the quality of care and cost effects of IBD patients were assessed in a healthcare professional electronic survey (conducted in 2017) and in an analysis of hospital district administrative data, respectively. Hospital district administrative data were obtained from eight districts covering years from 2008 to 2016, and comprised all hospitalisation and outpatient data for a population of 1.34 million. Results: Forty-nine physicians (gastroenterologists 47%) and 88 nurses (IBD nurses 26%) responded to the survey. Of the physicians, 92% reported that established IBD nurse had released physician's resources by consulting patients independently. The most important IBD nurse contributions listed were patient support and follow-up (79–81% of the respondents). The role of specialised IBD nurse role were established in four out of eight healthcare districts. IBD clinics with an established IBD nurse produced more patient contacts, but a larger proportion of the contacts was managed by IBD nurse and a smaller share was escalated to physicians appointments. Also, larger proportion of patient were contacted remotely. Clinics with an established IBD nurse had reported less patient hospitalisation (4–9% vs. 11–19%). Estimated annual cost savings in IBD care ranged between 43 300 and 453 600€ in clinics with an established IBD nurse. Conclusions: The introduction of an established IBD nurse led to better quality of care and potentially significant cost savings by improving patients' access to care, reducing hospitalisation and reallocating physician's time resources.